ANALISIS NILAI MORAL DAN NILAI PENDIDIKAN KARAKTER DALAM CERITA RAKYAT ASAL MULA DANAU BATUR - Sri Fitriwati Andi Patangai (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the moral values and character education values contained in the folklore The Origin of Lake Batur. The research employed a descriptive qualitative method using a content analysis approach. The data consisted of words, phrases, and sentences in the folklore that reflect moral values and character education values. The data source was a collection of Indonesian folklore written by Yudhistira Ikranegara. Data were collected through reading and note-taking techniques, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the folklore The Origin of Lake Batur contains moral values related to responsibility, conscience, and obligation. In addition, character education values identified in the story include religious values, moral values, and social values. These values are reflected through the characters’ behaviors, interactions among characters, and narrative events within the story. The findings suggest that The Origin of Lake Batur has strong potential as instructional material for literary learning and character education in educational settings.